2020
DOI: 10.1021/acs.joc.0c01377
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Acyl Fluorides from Carboxylic Acids Using NaF-Assisted Deoxofluorination with XtalFluor-E

Abstract: The synthesis of acyl fluorides using the deoxofluorination reaction of carboxylic acids using XtalFluor-E is described. This transformation, assisted by a catalytic amount of NaF, occurs at room temperature in EtOAc, where XtalFluor-E behaves as the activating agent and the fluoride source. A wide range of acyl fluorides were obtained in moderate to excellent yields (36–99%) after a simple filtration on a pad of silica gel. We also demonstrated that sequential deoxofluorination/amidation was possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 40 publications
(72 reference statements)
0
26
0
Order By: Relevance
“…These fluorochemicals are hydrolysis products of LiPF 6 with H 2 O. [12e] Besides, a new peak appeared at 16.8 ppm in BA-added electrolyte corresponds to R-COF, [17] produced by the reaction of BA with HF. These outcomes confirm that additive BA can scavenge HF completely and effectively inhibit the decomposition of LiPF 6 .…”
Section: Resultsmentioning
confidence: 99%
“…These fluorochemicals are hydrolysis products of LiPF 6 with H 2 O. [12e] Besides, a new peak appeared at 16.8 ppm in BA-added electrolyte corresponds to R-COF, [17] produced by the reaction of BA with HF. These outcomes confirm that additive BA can scavenge HF completely and effectively inhibit the decomposition of LiPF 6 .…”
Section: Resultsmentioning
confidence: 99%
“…Moderate to excellent yields were obtained by using catalytic quantities of sodium fluoride starting with both aliphatic and aromatic carboxylic acids (Scheme 11a). 28 Although acyl fluorides can be purified simply by filtration over silica gel, it has also been demonstrated that a sequential amidation could be achieved directly without purification of the intermediate acyl fluorides (Scheme 11b).…”
Section: Short Review Synthesismentioning
confidence: 99%
“…In addition to our direct cross-coupling reaction method, several useful synthetic methods for the formation of acyl fluorides have become available in recent years [19][20][21][22][23]. In this context, we were interested in the functional transformation of an acyl fluoride unit into a CF 3 motif.…”
Section: Introductionmentioning
confidence: 99%